正畸治疗与牙周硬组织健康的关系及处理 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2019)
Periodontal tissue, especially the alveolar bone, are closely associated with the progress and efficacy of orthodontic treatment. Prior to and during orthodontic treatment, dentists should fully evaluate the status of periodontal hard tissues to prevent clinical problems. This article aims to discuss bone issues associated with orthodontic treatment, including gingival papilla absence, alveolar bone insufficiency, excessive cortical resistance, and altered passive eruption, etc. The mechanism and prevention methods of these problems are also described.